THE POLITICAL COMMUNICATION STRATEGY OF WOMEN IN THE GERINDRA PARTY IN LAMPUNG PROVINCE DURING THE 2024 ELECTION - Ria, Dwita; Poernomo, Marlinda Irwanti; Putri, Gita Leviana; Kesuma, Mezan el-Khaeri (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
The purposed of this research is to analyze ow do female politicians from Partai Gerindra in Lampung utilize communication strategies based on discourse theory to enhance their political representation and challenge the prevailing masculine political discourse. The method employed in this research is a qualitative case study approach that utilizes in-depth interviews, observations, and document analysis to explore the political communication strategies of female candidates from the Gerindra Party in Lampung Province. The research findings reveal that female political candidates effectively enhance their communication strategies through inclusive messaging, language sensitivity, social media engagement, and personal branding to build trust and connect authentically with diverse audiences, highlighting the importance of adapting their approaches to meet the cultural and educational needs of their constituents.gb777